Urgence of E-Sport Regulation in Creative Economy in the National Industrial Sector - Wibisono, Javier Farizi; Setiawan, Rachmad Gusti; Novita R, Uul; Marchelia, Andria (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The goal of this study is to analyze Law Number 24 of 2019 concerning the Creative Economy and Law Number 3 of 2014 concerning Industry in accommodating e-sport as a creative industry in Indonesia, and to analyze the urgency of establishing regulations that specifically regulate e-sport in the creative industry in Indonesia. This research is normative legal research by conducting a literature study. This research was conducted by processing sources of legal material supported by concepts and theories to obtain solutions to the main problems studied. From the results of this study it can be concluded that e-sports in its implementation do not meet the elements contained in the definition of Industry in Law Number 3 of 2014 concerning Industry, e-sports are in line with Article 1 of Law Number 24 of 2019 concerning the Creative Economy which the embodiment of additional value in e-sports is a form of utilizing games which are an objects and humans as subjects in the form of competition which indirectly creates an environment for the parties involved in it. Therefore, there is an urgency to formalize a regulation that specifically regulate e-sport. Regulations are needed to clarify the position of e-sports, that e-sports should be categorized as a sport or as an industrial sector. Because at this time e-sport are currently subject to Law Number 3 of 2005 concerning the National Sports System, but there are some elements that are not suitable as a sport.